The burden of transport injury and risk factors in India from 1990 to 2019: evidence from the global burden of disease study - Deepak Kumar Behera; Sanjay Kumar Singh; Dinesh Kumar Choudhury (BMC, 2022)
Abstract Background India is one of the fastest-growing developing economies associated with many socio-demographic challenges that include a high density of population, growing urbanization, and poor road infrastructure. These challenges might lead to the cause of injury, especially transport related. Therefore, we aim to analyze the burden of Transport Injury (TI) and associated risk factors in India using the required data from 1990 to 2019. Methods This study has used the latest Global Burden of Disease Study (GBD) 2019 data set and estimated TI-related incidence rate, mortality (death) rate, and Disability-Adjusted Life Years (DALYs) lost for India over the period from 1990 to 2019. The latest round of GBD survey-2019 provides information about 369 diseases and injuries and 87 risk factors across age groups and gender. Results Around 25% of the death rate of all ages was caused due to TI in 2019, significantly higher than in 1990 (20%). However, between 1990 and 2019, the DALYs rate per 100,000 people due to TI decreased slightly by 1.6% for all ages and both gender while more reduction has been observed in under 5- and 5-14-years age groups. On the contrary, the incidence rate and DALYs rate had increased substantially in the age group above 50 years which could be a serious issue for the safety of aging people. By analyzing the sub-cause of TI, we found that motorcyclist road injuries and pedestrian road injuries have been major causes of deaths in India during the last three decades. Further, we have found four risk factors associated with environmental change, occupational hazard, behavioral risk, and metabolic risk that cause TI injuries. Conclusions TI-related disease burden has not been reduced over the years in India despite improvements in road infrastructure and digital technology. Improvement in transport policies; awareness about traffic rules and laws among citizens, and improvement in governance in the road & transport sector could change the behavioral risk factors of TI and reduce population unwanted death and suffering.